Effect of phosphorus and FYM on yield and uptake of nutrients in pearl millet - SANDEEP SINGH; TAHIR MOHD CHAUHAN (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during kharif 2015-16 at Panwari village, Agra, Uttar Pradesh to study the effect of four graded levels of FYM (0, 5, 10 and 15 t/ha) and phosphorus (0, 20, 40 and 60 kg P2O5 /ha) on yield, quality and uptake of nutrients in pearl millet (Pennisetum glaucum L). Results revealed that the growth and yield attributes of pearl millet increased significantly with the application of FYM up to 10 t/ha and fertilizer P up to 40 kg P2O5/ha. The results indicated the superiority of integrated use of FYM and fertilizer phosphorus in increasing the productivity of pearl millet compared to application of fertilizer P alone. Protein content and yield in grain increased significantly with the application of 60 kg P2O5 /ha and 10 t FYM /ha over their respective controls. The uptake of N, P and K by pearl millet grain and stover increased significantly with increasing levels of P over control. The amounts of organic carbon, available N and P in post harvest soil increased significantly with the increasing levels of both FYM and phosphorus.